The biological properties of three trichothecene mycotoxins produces by fusaris - Janse Van Rensburg, Daniel Francois (Division of Medical Biochemistry and Structural Biology, 2018)
The highly toxic fungal metabolite, neosolaniol monoacetate, was isolated and purified from cultures of Fusarium sambucinum. Since little is known about its toxic properties, the biological effects of this trichothecene were compared to those caused by diacetoxy-scirpenol in male Wistar rats. The lesions caused by the two toxins were very similar. Chronic exposure to either toxin led to a significant decrease (P<0.05) in red blood cell counts and a significant increase (P<0.05) in platelet size. The major pathological lesions observed were atrophy of the actively dividing cells of the bone marrow, thymus, spleen and lymph nodes. The reported species difference in T-2 toxin toxicity was investigated by determining the deacylation rate of T-2 toxin to HT-2 toxin, one of the first steps in the detoxification of this trichothecene. The high deacylation rate catalysed by rat microsomes correlated with the low sensitivity of this species to T-2 toxin, whereas the low deacylation rates with cat and monkey microsomes agreed with their high sensitivity. In contrast to this, the apparently high toxicity of T-2 toxin to humans does not correlate with the high deacylation rate observed in human hepatic microsomes. Involvement of the UDP-glucuronyltransferases in the detoxification of T-2 toxin was studied with rat and pig hepatic microsomes. T-2 toxin and two of its metabolites, HT-2 toxin and T-2 tetraol, did not appear to act as substrates for these enzymes under the in vitro conditions used.